ABNORMAL UTERINE BLEEDING (AUB) - MODERN POSSIBILITIES OF OPTIMIZATION OF TACTICS OF TREATMENT - Yu. Yu. Tabakman; A. G. Solopova; A. Kh. Bishtavi; S. O. Smirnova; A. A. Kocharian (IRBIS LLC, 2016)
Abnormal uterine bleeding is one of the most frequent manifestations of diseases of female genital organs and cause 2/3 of all hysterectomies. The results of study of the surgical specimens show that 40-69% of patients not detected no organic changes. In these cases, hysterectomy may be considered excessive interference that leads to an unjustified increase the cost of treatment and risk of complications. It is very important to determine the optimal volume of diagnostic procedures necessary to exclude and/or reduce the number of unnecessarily radical surgery in patients with AUB according to the modern nomenclature AUB.